Simulation of fluid spraying processes in a device for automatic control of anaerobic fermentation process parameters in biogas reactors - M. Zablodskiy; D. Babak (Machinery & Energetics, 2025)
The relevance of the study is justified by the rapid development of biogas technologies, which requires continuous improvement of methods and equipment to increase efficiency and ensure optimal productivity of the biogas and biomethane production process. The aim of this research was to improve and optimise devices for automatic control of anaerobic fermentation process parameters in biogas reactors. Methods of mathematical modelling of the 3D model in the Ansys Fluent environment, as well as methods of experimental studies to determine the spray spectrum of nozzles, jet distribution and the shape of the fluid spray cone were used. A constructive scheme of the device for automatic control of the parameters of the anaerobic fermentation process in biogas reactors, a mathematical model of the process of fluid spraying in the sensor cleaning system, which used equations describing the evolution of the kinetic energy of turbulence and the frequency of turbulence, are proposed. An automatic recorder capable of measuring voltage, current, and pressure with a frequency of about 120 measurements per second was created, which insures a high-precision removal of the load characteristics in the fluid supply system. Based on the results of modelling and experimental studies, the patterns of jet distribution and the shape of the fluid spray cone depending on the change in the diameters of the spray nozzles, were established. The simulation results demonstrated the high accuracy and reliability of the mathematical model, which was an important prerequisite for further complex simulation and optimisation. This study makes a significant contribution to the development of more efficient methods and means of automatic control of the parameters of the anaerobic fermentation process in biogas reactors, contributing to an increase in the productivity of the biogas production process